2016
DOI: 10.7554/elife.12192
|View full text |Cite
|
Sign up to set email alerts
|

A common mechanism underlies changes of mind about decisions and confidence

Abstract: Decisions are accompanied by a degree of confidence that a selected option is correct. A sequential sampling framework explains the speed and accuracy of decisions and extends naturally to the confidence that the decision rendered is likely to be correct. However, discrepancies between confidence and accuracy suggest that confidence might be supported by mechanisms dissociated from the decision process. Here we show that this discrepancy can arise naturally because of simple processing delays. When participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
372
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(419 citation statements)
references
References 62 publications
43
372
4
Order By: Relevance
“…They were allowed to adjust their gaze to the desired level before finalizing their combined choice and confidence report (Figure 5A). We thus encouraged subjects to use all available information in the 200 ms stimulus for both reports (Van den Berg et al, 2016). The results from the human observers were similar to those from the monkey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were allowed to adjust their gaze to the desired level before finalizing their combined choice and confidence report (Figure 5A). We thus encouraged subjects to use all available information in the 200 ms stimulus for both reports (Van den Berg et al, 2016). The results from the human observers were similar to those from the monkey.…”
Section: Resultsmentioning
confidence: 99%
“…Confidence in the decision derives from a mapping between the DV and the probability that a decision based on this DV will be correct. The mapping is thought to incorporate the decision time or the state of the competing (losing) accumulator(s), or both (Vickers, 1979; Kiani and Shadlen, 2009; Zylberberg et al, 2012; Kiani et al, 2014; Van den Berg et al, 2016). The noisiness of the momentary evidence causes the DV to wander from its starting point, as in Brownian motion or diffusion, whereas the expectation (i.e., mean) of the momentary evidence increments or decrements the DV deterministically.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological and microstimulation studies in behaving monkeys have revealed that the very same neurons that encode the decision variable also encode a confidence signal (Fetsch, Kiani, Newsome, & Shadlen, 2014;Kiani & Shadlen, 2009). Recent behavioral and computational evidence suggest that changes of mind in decision-making and confidence are linked by a common generative mechanism (Van den Berg et al, 2016). In the drift diffusion model framework, confidence corresponds to the log posterior odds of a correct response and can be derived from the diffusion process using Bayes' rule (Kiani & Shadlen, 2009).…”
Section: Emg Activity and The Decision Variablementioning
confidence: 99%
“…For example, we might ignore evidence contradicting the option that we chose ("confirmation bias" [27]), increase our confidence in predicted outcomes that seem to have a consistent pattern (the "illusion of validity" [10]), underestimate our probability of being correct in hard scenarios, and overestimate it in easier situations (the "hard-easy effect" [26]). Among this rich repertoire of cognitive illusions, the most widespread is "overconfidence" [28]. This bias is particularly harmful when it is present among experts, such as forecasters [53] and policy makers [54], and a deeper understanding of its cognitive origin may help us guard against it.…”
Section: Box 1 Distortions Of Confidencementioning
confidence: 99%
“…In addition, knowing the right time to gauge the validity of our choices is essential for minimising distortions of confidence [25] wherein confidence is no longer predictive of objective accuracy (Box 1). These include overconfidence [26] and confirmation bias [27]; both are systematically observed in human choices, and both contribute to poor judgement and bad decisions [28].…”
Section: Introductionmentioning
confidence: 99%